Pembuatan Instrumen Teknologi Perencanaan Menu Diet - Pratiwi Hariyani Putri; Fildzah Karunia Putri; Endang Sulistiyani (Preventia : The Indonesian Journal of Public Health, 2020)
This study aims to create a Diet Menu Planning Technology Instrument. The model used for making the instrument is procedural. This model is a descriptive model with a description of the development steps according to the research needs. R and D was chosen as the procedural approach. The development steps are (1) analysis of the weaknesses of the diet menu-planning instrument currently in use, (2) analysis of the instrument specifications for new technology, (3) instrument design, and (4) instrument testing. The resource persons in this study were lecturers of the nutrition study program and selected using purposive sampling technique to obtain data on the needs for dietary menu planning technology instruments. The types of data produced in this study are qualitative and quantitative data. The final product of this diet menu planning automatic instrument is named "Menu Harianku". This product is used as an instrument to assist the nutritional care process. The final product is a display of the food menu along with information on nutrients and percentage of fulfillment based on the nutrition needs of each individual. The results of the functionality test show a value of 100 percent, meaning that all the features available can work properly.